A Comparison Between The World Of Angels And The World Of Jinns - Al-Azmi, Khaled (Jordan Journal of Islamic Studies, 2023)
This work presents a comparison between the world of Angels and the world of Jinns. It starts shedding the light on the subject of the research by defining both concepts of Angels and jinns. Secondly, it demonstrates the similarities in both of them, which are: Both of Angels and Jinns are considered as knowledge of The Unseen. Both of Angels and Jinns have mind and able to think Both of them die. Both of them don’t know about The Unseen. Both of them have superior abilities that human doesn’t have. Thirdly, it shows the differences between the two concepts, which are: Angels are created from the light whereas Jinns are created from the fire. Angels have a natural propensity for obeying God and they are impeccable, whereas Jinns could be submitter or disobedient. In the first condition s/he deserves reward while in the second condition s/he deserves penalty. Angels do not eat or need to eat, whereas Jinns Angels do not marry or have progeny whereas Jinns Angels shelters are in the sky whereas Jinns shelters are on the earth.The research comes to a conclusion that, although there are differences between the world of Angels and the world of Jinns, an existing of similarities between both of them cannot be denied.